Angiosarcoma arising in the capsule of a mammary silicone implant. Issue 5 (7th January 2022) - Rajan, Sreekumar Sundara; Haider, Asma; Burrell, Helen; Whisker, Lisa; Tamimy, Muhammad; McCulloch, Tom; Lee, Andrew H. S.
Abstract: A 40‐year‐old woman with silicone implants inserted 21 years before presented with sudden onset of painful right breast swelling. Clinical examination revealed a firm swollen breast with appearance of old bruising. Ultrasound showed fluid around the implant. Cytology of the fluid showed cells with large pleomorphic nuclei with prominent nucleoli including elongated forms and very occasional vacuoles. The cell block also contained small fragments with atypical spindle cells around slit‐like spaces that were positive for CD31 and CD34. MRI showed a 25 mm serpiginous area of enhancement on the inner aspect of the fibrous capsule with haematoma between the capsule and the implant. The capsule and adjacent area were excised. Histology showed angiosarcoma extending from the inner aspect of the capsule into the cavity around the implant. The location of the tumour on the inner aspect of the capsule is the same site that breast implant associated anaplastic large cell lymphomas arise and suggests a possible causal link between the implant and the angiosarcoma. This case emphasises the value of cytological assessment of fluid around breast implants and the role of cell blocks and immunohistochemistry.